2003
DOI: 10.1177/014556130308200119
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cell Granuloma of the Thyroid with Hashimoto's Thyroiditis: Report of a Rare Case

Abstract: As only eight cases have been p reviously reported in the literature, plasma cell granuloma of the thyroid gland is a rare entity. This condition can be conf used with a benign or malignant neoplastic thyroid process. In this article, we describe a new case ofplasma cell granuloma of the thyroid gland that occurred in a 46-year-old man who also had Hashim oto 's thyroiditis. This case represents only the second documented instan ce of a plasma cell granuloma of the thyroid occurring in the setting of Hashimoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…All of these reported cases were benign and did not show recurrences; (3) histologically, except for our case, all 14 previously reported cases were PCG; and (4) immunohistochemical study demonstrated that there were no ALKpositive cells in any of the four cases including our cases examined [14,19]. However, ALK gene rearrangement was detected in neither of the reported cases.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…All of these reported cases were benign and did not show recurrences; (3) histologically, except for our case, all 14 previously reported cases were PCG; and (4) immunohistochemical study demonstrated that there were no ALKpositive cells in any of the four cases including our cases examined [14,19]. However, ALK gene rearrangement was detected in neither of the reported cases.…”
Section: Discussionmentioning
confidence: 45%
“…As previously suggested [14,17], the clinical behavior and ALK negativity of the IPT of thyroid gland indicated that the thyroidal counterpart of IPT is a reactive rather than neoplastic lesion.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…PCG is a non-neoplastic proliferation of plasma cells within a fibrous stroma with unknown etiology. PCG of the thyroid gland is very rare [79]. However, PCG of the thyroid gland is occasionally associated with HT [79].…”
Section: Discussionmentioning
confidence: 99%